2018
DOI: 10.1159/000491584
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Serum Exosomal miR-125b Level as a Potential Marker for Poor Prognosis in Intermediate-Risk Acute Myeloid Leukemia

Abstract: Background: The prognostic significance of miR-125b in intermediate-risk acute myeloid leukemia has not been well investigated. The aim of the study was to reveal the relationship between the elevated exosomal miR-125b level and the poor prognosis in adult patients with this disease. Methods: A total of 154 consecutive patients with intermediate-risk acute myeloid leukemia were enrolled. Exosomes were isolated from blood specimens. The exosomal miR-125b level was determined using quantitative real-time polymer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…In particular, they found that exosomal miR-125b was higher in patients at diagnosis with respect to healthy subjects. Moreover, miR-125b increased levels correlated with higher risks of relapse and overall death, supporting its role as an independent prognostic indicator in this intermediate-risk group of patients [87].…”
Section: Myeloid Neoplasmsmentioning
confidence: 73%
See 1 more Smart Citation
“…In particular, they found that exosomal miR-125b was higher in patients at diagnosis with respect to healthy subjects. Moreover, miR-125b increased levels correlated with higher risks of relapse and overall death, supporting its role as an independent prognostic indicator in this intermediate-risk group of patients [87].…”
Section: Myeloid Neoplasmsmentioning
confidence: 73%
“…EV miRNAs were also suggested as potential biomarkers in AML [37,81,[86][87][88]. Analysis of miR-155, a miRNA deregulated in this neoplasm [89], showed its significant higher level in serum MVs from 11 AML patients at diagnosis compared to healthy subjects; moreover, ROC curve analysis revealed that miR-155 could be a new potential diagnostic biomarker in AML [37].…”
Section: Myeloid Neoplasmsmentioning
confidence: 96%
“…Acute leukemia-derived EVs contain a variety of non-coding RNAs supporting leukemogenesis and influencing the outcome and response to therapy through the regulation of several genes involved in the pathogenesis of this disease [56] . In addition, several studies have highlighted the promising role of circulating miRs as biomarkers in acute myeloid leukemia (AML) ( Table 1 ) [4] , [34] , [74] , [82] , [85] . For instance, Marcucci and colleagues, by using nCounter assay, demonstrated that miR-155 overexpression was independently associated to poor prognosis in a large cohort of adult AML patients with normal karyotype [45] .…”
Section: Functional Interpretation Of Evs Content In Hmmentioning
confidence: 99%
“…Noting that, miR-125b to be proposed as an important biomarker for predicting the rate of disease remission and the risk of relapse. 140 Attempts to use DCs for the vaccination of leukemia patients have appeared to bring some interesting results. Hus et al 141 discussed the potential effects of autologous DC-based vaccination against CLL in 2008.…”
Section: Exosomes Effect On Leukemia Treatmentmentioning
confidence: 99%
“…Interestingly, a prior study focusing on serum exosomal miRNA‐125b in AML patients identified an up‐regulation of this miRNA to be strongly associated with elevation of relapse and risk of mortality. Noting that, miR‐125b to be proposed as an important biomarker for predicting the rate of disease remission and the risk of relapse 140 . Attempts to use DCs for the vaccination of leukemia patients have appeared to bring some interesting results.…”
Section: Exosomes Effect On Leukemia Treatmentmentioning
confidence: 99%